Prospect of Energy Link Between Central Asia and China: A Study on the Development of 'Energy Silk Route,' the Turkmenistan - China Pipeline - Kamiya, Masato (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: As the global economy grows at an unprecedented pace and with broader interactions among states and populations, energy has become an increasingly critical issue. Historically, energy resources have been a source of competition and discord among states, rather than a focus of cooperation. In fact, states have gone to war pursuing energy resources available within other nation states. In the contemporary world, states have agreements with others for energy cooperation and sharing infrastructures, and global markets to exchange energy commodities have been developed. However, the system for distributing energy resources that are spread unequally throughout the world still require greater investment and more effective strategies to allocate capital and technology to mitigate conflicts and create opportunities for stakeholder cooperation. Meanwhile, debates over energy issues are often complicated by various factors related to politics, economics and technology, and the confusion that stems from many these various aspects often conceals fundamental issues and hinders the establishment of appropriate policies. This thesis emphasizes the economic rationale of the development of a new international energy infrastructure and examines the reasons why stakeholders make huge investments to transport energy resources across national borders.